Evaluating the Usability of Virtual Tour Application Using the System Usability Scale (SUS) Method - Nur Cahyo Wibowo; Tri Lathif Mardi Suryanto; Mu'tasim Billah; Fajar Annas (International Journal of Computer, Network Security and Information System, 2022)
UPN